Anti-cracking pavement base material, preparation method and construction process

CN116715475BActive Publication Date: 2026-10-20JINAN JINYUE HIGHWAY ENGINEERING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310784565.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2026-10-20
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

半刚性基层产生的收缩裂缝会使路面结构层承载能力降低,最终导致路面结构层整体损坏

Benefits of technology

[0019]1、本发明提供的防裂路面基层材料,沥青改性后可以增强沥青的粘结力和延展性,提高基层的防裂性能;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of anti-cracking pavement base material, preparation method and construction process, belong to building material field.The pavement base material includes the following weight percentage components: cement 5~8%, steel fiber 0.5~1%, two-way fiber mesh 0.3~0.5%, nano zinc oxide 1~3%, activator 1~2%, water 6~10%, and the balance is cementing material;The cementing material is made of gravel, fly ash, modified asphalt with 15~20:3~5:1~3 mass ratio compounding and compacting.The anti-cracking pavement base material of the application has good compressive strength and good anti-cracking performance, fully meets the requirements of highway subgrade and paving layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials, specifically relating to a crack-resistant road base material, its preparation method, and its construction process. Background Technology

[0002] With the rapid growth of highway traffic in my country, vehicle overloading is widespread, and the new traffic conditions place increasingly higher demands on the load-bearing capacity of road surfaces. Because semi-rigid base materials possess good mechanical properties, high early strength, strong plate-like structure, and certain flexural tensile strength, good water stability, frost resistance, and fatigue resistance, semi-rigid base materials have become the main form of asphalt pavement structure for highways in my country.

[0003] However, it also has some drawbacks in road use. For example, it is sensitive to changes in temperature and humidity, and is prone to shrinkage cracks under alternating temperature and humidity conditions. Shrinkage cracks in semi-rigid base layers reduce the load-bearing capacity of the pavement structure, ultimately leading to overall damage. The degree of cracking in semi-rigid base layers varies under different environmental factors. The main environmental factors affecting cracking in semi-rigid base layers are temperature and humidity. If semi-rigid base layers are not properly cured after construction, the large amount of moisture evaporates from the base material, easily causing drying shrinkage cracks. If the temperature drops sharply, thermal shrinkage cracks are likely to appear in the base layer under temperature stress. Shrinkage cracks in semi-rigid base layers, under the influence of vehicle loads and cyclical environmental factors, can cause significant stress concentration at the crack tip, leading to reflective cracks extending upwards from the bottom of the surface layer. The appearance of cracks provides a channel for surface water to enter the surface layer. Surface water continuously enters the pavement structure layer through cracks and, unable to drain in time, stagnates between the surface layer and the base layer. Under the repeated action of vehicle loads, the dynamic water pressure erodes the base layer, causing the base layer material to detach and loosen, reducing the adhesion between the base layer and the surface layer, decreasing the load-bearing capacity of the pavement structure layer, and ultimately leading to the overall damage of the pavement structure layer. Therefore, cracking of the semi-rigid base layer leading to asphalt pavement cracking is one of the main causes of asphalt pavement damage. In addition to strictly adhering to the cement dosage, gradation range, and optimum moisture content specified in the mix design during the construction of the semi-rigid base layer, timely curing after construction can significantly reduce shrinkage cracks in the base layer.

[0004] Therefore, preventing cracks in semi-rigid base courses is crucial for extending the service life of highways. Improving the crack resistance of pavement base materials and construction techniques is of great significance for extending the service life of semi-rigid base asphalt pavements, reducing maintenance costs, and improving the service quality of highways. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a crack-resistant pavement base material, its preparation method, and its construction process. It possesses good compressive strength and excellent crack resistance, fully meeting the requirements of highway subgrades and pavements.

[0006] This invention provides a crack-resistant road base material, which comprises the following components by weight percentage: 5-8% cement, 0.5-1% steel fiber, 0.3-0.5% biaxial fiber mesh, 1-3% nano zinc oxide, 1-2% activator, 6-10% water, and the balance being binder; the binder is composed of crushed stone, fly ash, and modified asphalt mixed and compacted in a mass ratio of 15-20:3-5:1-3.

[0007] Another aspect of the present invention provides a method for preparing a crack-resistant pavement base material, the method comprising the following steps:

[0008] S1. Thoroughly mix the binder, steel fiber, and nano zinc oxide to obtain a mixture;

[0009] S2. Add the activator to water and stir evenly, then add it to the cement and stir evenly to obtain cement activating mixture;

[0010] S3. The mixture and the aggregate are fed into a forced mixer and mixed evenly to obtain a base layer mixture.

[0011] S4. The base mixture is bonded to the surface of the bidirectional fiber mesh to obtain the crack-resistant road base material.

[0012] In another aspect, the present invention provides a construction process for a crack-resistant pavement base material, the construction process comprising the following steps:

[0013] Step 1: Moisten the road subbase with water, then transport the crack-resistant pavement base material to the top layer of the roadbed and pave it in stages using a paver;

[0014] Step 2: Use compaction equipment to compact the material, following the sequence of initial compaction, intermediate compaction, and final compaction.

[0015] Step 3: After the compaction test is passed, a plastic film needs to be covered on the top surface of the base layer. During the curing stage, water should be sprayed to maintain moisture and meet the required humidity.

[0016] Step 4: After the base layer construction is completed, compressive strength and crack resistance tests are conducted at different locations every 7 days to ensure that all indicators are within the specified range and the requirements are met before the upper layer is laid.

[0017] In another aspect, the present invention provides the above-mentioned crack-resistant pavement base material, or the crack-resistant pavement base material prepared by the above-mentioned method for preparing crack-resistant pavement base material, or the application of the above-mentioned construction technology of crack-resistant pavement base material in highway asphalt pavement.

[0018] The beneficial effects of the present invention include at least one of the following:

[0019] 1. The crack-resistant road base material provided by this invention can enhance the adhesion and ductility of asphalt after asphalt modification, thereby improving the crack resistance of the base layer;

[0020] 2. The crack-resistant road base material provided by the present invention can enhance tensile strength and ductility and inhibit the propagation of microcracks by adding steel fibers;

[0021] 3. The crack-resistant pavement base material provided by the present invention, by bonding a bidirectional fiber mesh to the surface of the base material, can inhibit the propagation of cracks and enhance the bearing capacity of the pavement;

[0022] 4. The crack-resistant road base material provided by this invention can significantly enhance the strength and compressive strength of the base layer and improve its crack resistance by adding nano zinc oxide;

[0023] 5. The preparation method of the crack-resistant pavement base material of the present invention produces a base material whose components work synergistically with each other, exhibiting good compressive strength and excellent crack resistance, fully meeting the requirements of highway subgrade and pavement;

[0024] 6. The preparation method of the crack-resistant pavement base material of the present invention uses batch raw materials and industrialized equipment, is highly versatile, easy to scale up production, and has a good prospect for industrial application.

[0025] 7. The construction process of the crack-resistant pavement base material of the present invention allows the pavement base material to be formed at room temperature without the need for hot-mix construction conditions. Its construction conditions are simple, the cost is low, and the impact on the construction environment during construction is small, which is conducive to its widespread use. Detailed Implementation

[0026] To more clearly illustrate the overall concept of the present invention, a detailed description is provided below using examples.

[0027] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0028] In this invention, unless otherwise expressly specified and limited, the first feature "on" or "below" the second feature may be in direct contact with the first and second features, or indirect contact through an intermediate medium. In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0029] In the following sections, the crack-resistant pavement base material, preparation method, and construction process of the present invention will be described in detail with reference to exemplary embodiments.

[0030] In an exemplary embodiment of the present invention, the method for preparing the crack-resistant pavement base material can be achieved through the following steps:

[0031] S1. Thoroughly mix 0.5-1% by weight of steel fiber, 1-3% by weight of nano zinc oxide and binder to obtain a mixture.

[0032] Specifically, the binder is composed of crushed stone, fly ash, and modified asphalt in a mass ratio of 15–20:3–5:1–3, which is then compacted. The modified asphalt is prepared by the following steps: asphalt is heated to 165–170°C to form a fluid; then, SBS thermoplastic elastomer, styrene resin, and mineral powder are added to the fluid, and the mixture is stirred at 165–170°C for 60–90 minutes to obtain the modified asphalt. The mass ratio of asphalt, SBS thermoplastic elastomer, styrene resin, and mineral powder is 70–80:8–12:5–10:2–4. The steel fibers are 12 mm long and 0.2 mm in diameter. The addition of thermoplastic elastomer improves the elasticity and toughness of the asphalt, enhancing its low-temperature performance, fatigue resistance, and crack repair ability. The addition of thermosetting resin increases the hardness and cross-linking density of the modified asphalt, improving its high-temperature performance and resistance to deformation. The addition of mineral powder increases the volume and thixotropy of the asphalt, enhancing its durability and self-healing ability. Modified asphalt enhances the adhesion and ductility of asphalt, improves the crack resistance of the base course, and exhibits good high-temperature performance. Adding steel fibers enhances tensile strength and ductility, and inhibits microcrack propagation. Adding nano-zinc oxide significantly enhances the strength and compressive strength of the base course, improving its crack resistance.

[0033] S2. Add 1-2% by weight of activator to 6-10% water and stir evenly. Then add it to 5-8% cement and stir evenly to obtain cement activator mixture.

[0034] Specifically, the activator is any one of calcium chloride, magnesium chloride, or magnesium chloride; however, the present invention is not limited thereto. The addition of the activator can accelerate the hydration and hardening of cement, enabling it to gain strength more quickly and reducing the formation of cracks.

[0035] S3. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0036] S4. The base mixture is bonded to the surface of a two-dimensional fiber mesh at a weight percentage of 0.3-0.5% to obtain the crack-resistant pavement base material.

[0037] Specifically, the bidirectional fiber mesh is a sheet-like grid woven from chopped polyester fibers with a length of 6–12 mm and a strength greater than 2000 MPa, with a mesh size of 1 cm × 1 cm. The bidirectional fiber mesh is gently laid on the surface of the incompletely consolidated base course mixture and lightly compacted with a small roller to ensure strong adhesion between it and the base course mixture. Bonding the bidirectional fiber mesh to the surface of the base course material can inhibit crack propagation and enhance the pavement's load-bearing capacity.

[0038] The road base material prepared by the above method comprises the following components: 5-8% cement, 0.5-1% steel fiber, 0.3-0.5% biaxial fiber mesh, 1-3% nano-zinc oxide, 1-2% activator, 6-10% water, and the balance being binder; the density of the crack-resistant road base material is 1.4 g / cm³. 3 ~1.8g / cm 3 .

[0039] In another exemplary embodiment of the present invention, the construction process of the crack-resistant pavement base material can be achieved through the following steps:

[0040] Step 1: Moisten the road subbase with water, then transport the anti-crack road base material to the top layer of the roadbed and pave it in stages using a paver.

[0041] Step 2: Compact the surface using compaction equipment, following the sequence of initial compaction, intermediate compaction, and final compaction. In Step 2, the first compaction is performed using a double-drum roller, with 1-2 passes. The second compaction is performed using a vibratory roller, with 3-4 passes. The third compaction is performed using a rubber-tired roller, with 1-2 passes.

[0042] Step 3: After the compaction test is passed, a plastic film needs to be covered on the top surface of the base layer. During the curing stage, water should be sprayed to maintain moisture and meet the required humidity level.

[0043] Step 4: After the base layer construction is completed, compressive strength and crack resistance tests are conducted at different locations every 7 days to ensure that all indicators are within the specified range and the requirements are met before the upper layer is laid.

[0044] Example 1

[0045] This embodiment prepares a crack-resistant pavement base material 1# using the following method:

[0046] S1. Heat 200 kg of asphalt to 165°C to form a fluid, then add 26 kg of SBS thermoplastic elastomer, 19 kg of styrene resin and 8 kg of mineral powder to the fluid, and stir at 165°C for 75 min to obtain modified asphalt.

[0047] S2. A binder is prepared by mixing and compacting 1500 kg of crushed stone, 400 kg of fly ash, and 200 kg of modified asphalt.

[0048] S3. Thoroughly mix 20.8 kg of steel fiber, 52 kg of nano zinc oxide and 2100 kg of binder to obtain a mixture.

[0049] S4. Add 39 kg of calcium chloride to 208 kg of water and stir until homogeneous. Then add it to 169 kg of cement and stir until homogeneous to obtain cement activating mixture.

[0050] S5. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0051] S6. Gently lay 10.4 kg of bidirectional fiber mesh on the surface of the incompletely consolidated base mixture, and gently compact it with a small road roller to make it bond firmly with the base mixture, thus obtaining crack-resistant pavement base material #1.

[0052] Example 2

[0053] In this embodiment, another crack-resistant pavement base material, #2, was prepared using the following method:

[0054] S1. Heat 200 kg of asphalt to 168°C to form a fluid. Then add 34.3 kg of SBS thermoplastic elastomer, 14.3 kg of styrene resin and 5.7 kg of mineral powder to the fluid and stir at 168°C for 60 min to obtain modified asphalt.

[0055] S2. 2250kg of crushed stone, 450kg of fly ash and 150kg of modified asphalt are mixed and compacted to obtain a binder.

[0056] S3. Thoroughly mix 16.53 kg of steel fiber, 33.06 kg of nano zinc oxide and 2850 kg of binder to obtain a mixture.

[0057] S4. Add 33.06 kg of magnesium chloride to 198.36 kg of water and stir until homogeneous. Then add it to 165.3 kg of cement and stir until homogeneous to obtain cement activating mixture.

[0058] S5. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0059] S6. Gently lay 9.92 kg of bidirectional fiber mesh on the surface of the incompletely consolidated base mixture, and gently compact it with a small road roller to make it bond firmly with the base mixture, thus obtaining crack-resistant pavement base material #2.

[0060] Example 3

[0061] In this embodiment, another crack-resistant pavement base material #3 was prepared using the following method:

[0062] S1. Heat 200 kg of asphalt to 170°C to form a fluid. Then add 30 kg of SBS thermoplastic elastomer, 25 kg of styrene resin and 10 kg of mineral powder to the fluid and stir at 170°C for 90 min to obtain modified asphalt.

[0063] S2. 1333 kg of crushed stone, 333 kg of fly ash, and 200 kg of modified asphalt were mixed and compacted to obtain a binder.

[0064] S3. Thoroughly mix 24.55 kg of steel fiber, 73.65 kg of nano zinc oxide and 1866 kg of binder to obtain a mixture.

[0065] S4. Add 49.1 kg of sodium chloride to 245.5 kg of water and stir until homogeneous. Then add it to 196.4 kg of cement and stir until homogeneous to obtain cement activating mixture.

[0066] S5. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0067] S6. Gently lay 12.28 kg of bidirectional fiber mesh on the surface of the incompletely consolidated base mixture, and gently compact it with a small road roller to make it bond firmly with the base mixture, thus obtaining crack-resistant pavement base material #3.

[0068] Example 4

[0069] In this embodiment, another crack-resistant pavement base material, #4, was prepared using the following method:

[0070] S1. Heat 216 kg of asphalt to 166°C to form a fluid, then add 27 kg of SBS thermoplastic elastomer, 24 kg of styrene resin and 7.5 kg of mineral powder to the fluid, and stir at 166°C for 70 min to obtain modified asphalt.

[0071] S2. 1512 kg of crushed stone, 294 kg of fly ash, and 210 kg of modified asphalt were mixed and compacted to obtain a binder.

[0072] S3. Thoroughly mix 17.21 kg of steel fiber, 36.89 kg of nano zinc oxide and 2016 kg of binder to obtain a mixture.

[0073] S4. Add 44.26 kg of calcium chloride to 172.13 kg of water and stir evenly. Then add it to 173 kg of cement and stir evenly to obtain cement activating mixture.

[0074] S5. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0075] S6. Gently lay 7.38 kg of bidirectional fiber mesh on the surface of the incompletely consolidated base mixture, and gently compact it with a small road roller to make it firmly bonded to the base mixture, thus obtaining the crack-resistant pavement base material 4#.

[0076] Example 5

[0077] This embodiment prepares another crack-resistant pavement base material, #5, using the following method:

[0078] S1. Heat 188 kg of asphalt to 165°C to form a fluid, then add 22.8 kg of SBS thermoplastic elastomer, 21.12 kg of styrene resin and 8.64 kg of mineral powder to the fluid, and stir at 165°C for 75 min to obtain modified asphalt.

[0079] S2. 1800 kg of crushed stone, 320 kg of fly ash, and 240 kg of modified asphalt are mixed and compacted to obtain a binder.

[0080] S3. Thoroughly mix 26.23 kg of steel fiber, 61.19 kg of nano zinc oxide and 2360 kg of binder to obtain a mixture.

[0081] S4. Add 43.71 kg of magnesium chloride to 233.12 kg of water and stir evenly. Then add it to 189.41 kg of cement and stir evenly to obtain cement activating mixture.

[0082] S5. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0083] S6. Gently lay 11.5 kg of bidirectional fiber mesh on the surface of the incompletely consolidated base mixture, and gently compact it with a small road roller to make it bond firmly with the base mixture, thus obtaining crack-resistant pavement base material #5.

[0084] Comparative Example 1

[0085] This comparative example prepared a crack-resistant pavement base material D1# using the following method:

[0086] S1. A binder is prepared by mixing and compacting 1500 kg of crushed stone, 400 kg of fly ash, and 200 kg of asphalt.

[0087] S2. Thoroughly mix 20.8 kg of steel fiber, 52 kg of nano zinc oxide and 2100 kg of binder to obtain a mixture.

[0088] S3. Add 39 kg of calcium chloride by weight to 208 kg of water and stir until homogeneous. Then add it to 169 kg of cement and stir until homogeneous to obtain cement activating mixture.

[0089] S4. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0090] S5. Gently lay 10.4 kg of bidirectional fiber mesh on the surface of the incompletely consolidated base mixture, and gently compact it with a small road roller to make it bond firmly with the base mixture, thus obtaining crack-resistant pavement base material D1#.

[0091] Comparative Example 2

[0092] Another crack-resistant pavement base material, D2#, was prepared using the following method:

[0093] S1. Heat 200 kg of asphalt to 165°C to form a fluid, then add 26 kg of SBS thermoplastic elastomer, 19 kg of styrene resin and 8 kg of mineral powder to the fluid, and stir at 165°C for 75 min to obtain modified asphalt.

[0094] S2. A binder is prepared by mixing and compacting 1500 kg of crushed stone, 400 kg of fly ash, and 200 kg of modified asphalt.

[0095] S3. Thoroughly mix 52 kg of nano zinc oxide and 2100 kg of binder to obtain a mixture.

[0096] S4. Add 39 kg of calcium chloride to 208 kg of water and stir until homogeneous. Then add it to 169 kg of cement and stir until homogeneous to obtain cement activating mixture.

[0097] S5. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0098] S6. Gently lay 10.4 kg of bidirectional fiber mesh on the surface of the incompletely consolidated base mixture, and gently compact it with a small road roller to make it bond firmly with the base mixture, thus obtaining crack-resistant pavement base material D2#.

[0099] Comparative Example 3

[0100] Another crack-resistant pavement base material, D3#, was prepared using the following method:

[0101] S1. Heat 200 kg of asphalt to 165°C to form a fluid, then add 26 kg of SBS thermoplastic elastomer, 19 kg of styrene resin and 8 kg of mineral powder to the fluid, and stir at 165°C for 75 min to obtain modified asphalt.

[0102] S2. A binder is prepared by mixing and compacting 1500 kg of crushed stone, 400 kg of fly ash, and 200 kg of modified asphalt.

[0103] S3. Thoroughly mix 20.8 kg of steel fiber and 2100 kg of binder to obtain a mixture.

[0104] S4. Add 39 kg of calcium chloride by weight to 208 kg of water and stir until homogeneous. Then add it to 169 kg of cement and stir until homogeneous to obtain cement activating mixture.

[0105] S5. The mixture and the mixed material are put into a forced mixer and mixed evenly to obtain a base mixture.

[0106] S6. Gently lay 10.4 kg of bidirectional fiber mesh on the surface of the incompletely consolidated base mixture, and gently compact it with a small road roller to make it bond firmly with the base mixture, thus obtaining crack-resistant pavement base material D3#.

[0107] Comparative Example 4

[0108] Another crack-resistant pavement base material, D4#, was prepared using the following method:

[0109] S1. Heat 200 kg of asphalt to 165°C to form a fluid, then add 26 kg of SBS thermoplastic elastomer, 19 kg of styrene resin and 8 kg of mineral powder to the fluid, and stir at 165°C for 75 min to obtain modified asphalt.

[0110] S2. A binder is prepared by mixing and compacting 1500 kg of crushed stone, 400 kg of fly ash, and 200 kg of modified asphalt.

[0111] S3. Thoroughly mix 20.8 kg of steel fiber, 52 kg of nano zinc oxide and 2100 kg of binder to obtain a mixture.

[0112] S4. Add 39 kg of calcium chloride to 208 kg of water and stir until homogeneous. Then add it to 169 kg of cement and stir until homogeneous to obtain cement activating mixture.

[0113] S5. The mixture and the aggregate are put into a forced mixer and mixed evenly to obtain crack-resistant pavement base material D4#.

[0114] The crack-resistant pavement base materials 1# to 5# prepared in Examples 1 to 5 and the crack-resistant pavement base materials D1# to D4# prepared in Comparative Examples 1 to 4 were tested for compressive strength and flexural strength according to the "Test Method for Unconfined Compressive Strength of Inorganic Binder Stabilized Materials" and "Test Method for Indirect Tensile Strength of Inorganic Binder Stabilized Materials (Split Split Test) (Test Specimens are Intermediate Specimens)" in JTG E51-2009, "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering". The test results are shown in Table 1.

[0115] Table 1

[0116] 1# 5.6 0.78 2# 4.5 0.70 3# 4.8 0.72 4# 5.4 0.75 5# 5.3 0.76 D1# 1.9 0.42 D2# 2.1 0.44 D3# 2.3 0.47 D4# 2.4 0.50

[0117] As shown in Table 1, the compressive strength and splitting strength of the road base materials in Examples 1-5 are much greater than those in Comparative Examples 1-4.

[0118] Compared with Comparative Examples 1-4, the difference in Comparative Example 1 is that no modified asphalt was added to its raw materials. The compressive strength and splitting tensile strength of the road base material in Example 1 are significantly greater than those in Comparative Example 1, indicating that the road base material made with modified asphalt in Example 1 has superior compressive and tensile strength. The addition of modified asphalt effectively improves the tensile strength of the road base material, thereby effectively improving its crack resistance. This is because: the addition of thermoplastic elastomers can improve the elasticity and toughness of asphalt, enhancing its low-temperature performance, fatigue resistance, and crack repair ability. The addition of thermosetting resins can increase the hardness and crosslinking density of the modified asphalt, improving its high-temperature performance and deformation resistance. The addition of mineral powder can increase the volume and thixotropy of the asphalt, enhancing its durability and self-healing ability. Modified asphalt enhances the adhesion and ductility of the asphalt, improving the crack resistance of the base layer.

[0119] The difference between Comparative Example 2 and Example 1 is that no steel fiber was added to Comparative Example 2. The compressive strength and splitting strength of the road base material in Example 1 are greater than those in Comparative Example 2. This indicates that the road base material made by adding steel fiber in Example 1 has better compressive strength and tensile strength. The reason is that steel fiber can be evenly dispersed in the base layer, play a supporting role, enhance tensile strength and elongation, and inhibit the propagation of microcracks.

[0120] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 did not add nano zinc oxide. The compressive strength and splitting strength of the road base material in Example 1 are greater than those in Comparative Example 3, indicating that the road base material prepared by adding nano zinc oxide in Example 1 has better compressive strength and tensile strength. This shows that nano zinc oxide can significantly enhance the strength and compressive strength of the base layer and improve its crack resistance.

[0121] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 did not add bidirectional fiber mesh. The compressive strength and splitting strength of the road base material in Example 1 are greater than those in Comparative Example 4, indicating that the road base material made by adding bidirectional fiber mesh in Example 1 has better compressive strength and tensile strength. This shows that bonding bidirectional fiber mesh to the surface of the base material can inhibit the propagation of cracks and enhance the bearing capacity of the road.

[0122] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.

Claims

1. A crack-resistant road base material, characterized in that, The road base material comprises the following components by weight percentage: 5-8% cement, 0.5-1% steel fiber, 0.3-0.5% biaxial fiber mesh, 1-3% nano zinc oxide, 1-2% activator, 6-10% water, and the balance being binder; The binder is composed of crushed stone, fly ash, and modified asphalt in a mass ratio of 15~20:3~5:1~3 and compacted. The modified asphalt is prepared by the following steps: heating asphalt to 165~170℃ to form a fluid, then adding SBS thermoplastic elastomer, styrene resin, and mineral powder to the fluid, and stirring at 165~170℃ for 60~90 min to obtain the modified asphalt. The mass ratio of the asphalt, SBS thermoplastic elastomer, styrene resin and mineral powder is 70~80:8~12:5~10:2~4.

2. The crack-resistant pavement base material according to claim 1, characterized in that, The bidirectional fiber mesh is a sheet-like mesh woven from polyester chopped fibers with a length of 6-12 mm and a strength greater than 2000 MPa.

3. The crack-resistant pavement base material according to claim 1, characterized in that, The activator is either calcium chloride or magnesium chloride.

4. A method for preparing the crack-resistant pavement base material according to claim 1, characterized in that, The preparation method includes the following steps: S1. Thoroughly mix the binder, steel fiber, and nano zinc oxide to obtain a mixture; S2. Add the activator to water and stir evenly, then add it to the cement and stir evenly to obtain cement activating mixture; S3. The mixture and the aggregate are fed into a forced mixer and mixed evenly to obtain a base layer mixture. S4. The base mixture is bonded to the surface of the bidirectional fiber mesh to obtain the crack-resistant road base material.

5. The method for preparing the crack-resistant pavement base material according to claim 4, characterized in that, The density of the crack-resistant pavement base material is 1.4 g / cm³. 3 ~1.8 g / cm 3 .

6. A construction process for the crack-resistant pavement base material according to claim 1, characterized in that, The construction process includes the following steps: Step 1: Moisten the road subbase with water, then transport the crack-resistant pavement base material to the top layer of the roadbed and pave it in stages using a paver; Step 2: Use compaction equipment to compact the material, following the sequence of initial compaction, intermediate compaction, and final compaction. Step 3: After the compaction test is passed, a plastic film needs to be covered on the top surface of the base layer. During the curing stage, water should be sprayed to maintain moisture and meet the required humidity. Step 4: After the base layer construction is completed, conduct compressive strength and crack resistance tests 7 days later to ensure that all indicators are within the specified range and meet the requirements before laying the upper layer.

7. The construction process of the crack-resistant pavement base material according to claim 6, characterized in that, In step two, the initial compaction is carried out using a vibratory roller, with 1 to 2 passes. The second compaction is carried out using a pneumatic tire roller, with 2 to 3 passes. The third compaction is carried out using a steel-drum vibratory roller, with 1 to 2 passes.

8. The application of a crack-resistant pavement base material as described in any one of claims 1 to 3, or a crack-resistant pavement base material prepared by the method described in claims 4 to 5, or a construction process of the crack-resistant pavement base material as described in claims 6 to 7, in highway asphalt pavement.

Citation Information

Patent Citations

  • Anti-cracking asphalt concrete and preparation method thereof

    CN112645642A